The effects of capital account liberalization and macroeconomic factors on firm-level stock returns volatilty in Malaysia - Saizal Pinjaman; Sarma Aralas (2018)
There are a number of research that have analysed the impact of financial liberalisation and macroeconomic factors on stock returns volatility. However, the results have been somewhat mixed. In the case of Malaysia, the current research estimates volatility using an EGARCH model where risk factors of stock returns are defined based on CAPM. Using dynamic panel data analysis from the years 1995 to 2013, our results suggest that interest rate has a positive relationship with stock returns volatility. In addition, economic development and exchange rate are found to have negative relationships with volatility. On the other hand, Consumer Price Index and money supply are found to be not statistically significant in influencing volatility. Further, the effect of capital account liberalisation is mixed, and dependent on the liberalisation indices used to measure liberalisation.